Insights into psychosis risk from leukocyte microRNA expression - Jeffries, C D; Perkins, D O; Chandler, S D; Stark, T; Yeo, E; Addington, J; Bearden, C E; Cadenhead, K S; Cannon, T D; Cornblatt, B A; Mathalon, D H; McGlashan, T H; et al. (Translational psychiatry, 2016)
Dysregulation of immune system functions has been implicated in schizophrenia, suggesting that immune cells may be involved in the development of the disorder. With the goal of a biomarker assay for psychosis risk, we performed small RNA sequencing on RNA isolated from circulating immune cells. We compared baseline microRNA (miRNA) expression for persons who were unaffected ( n =27) or who, over a subsequent 2-year period, were at clinical high risk but did not progress to psychosis ( n =37), or were at high risk and did progress to psychosis ( n =30). A greedy algorithm process led to selection of five miRNAs that when summed with +1 weights distinguished progressed from nonprogressed subjects with an area under the receiver operating characteristic curve of 0.86. Of the five, miR-941 is human-specific with incompletely understood functions, but the other four are prominent in multiple immune system pathways. Three of those four are downregulated in progressed vs. nonprogressed subjects (with weight -1 in a classifier function that increases with risk); all three have also been independently reported as downregulated in monocytes from schizophrenia patients vs. unaffected subjects. Importantly, these findings passed stringent randomization tests that minimized the risk of conclusions arising by chance. Regarding miRNA–miRNA correlations over the three groups, progressed subjects were found to have much weaker miRNA orchestration than nonprogressed or unaffected subjects. If independently verified, the leukocytic miRNA biomarker assay might improve accuracy of psychosis high-risk assessments and eventually help rationalize preventative intervention decisions.